Fast ion generation and its effect on ETB formation in the U-3M torsatron - Chechkin, V.V.; Grigor’eva, L.I.; Sorokovoy, E.L.; Sorokovoy, Ye.L.; Beletskii, A.A.; Slavnyj, A.S.; Burchenko, P.Ya.; Lozin, A.V.; Tsybenko, S.A.; Litvinov, A.P.; Kulaga, A.Ye.; Mironov, Yu.K.; et al. (Вопросы атомной науки и техники, 2006)
In the l=3 U-3M torsatron with RF produced and heated plasmas, a two-temperature ion energy distribution arises with a minor group of suprathermal ions. It is shown that a possible mechanism of fast ion generation is cyclotron heating and/or acceleration of ions by a strong RF field in the local Alfven resonance layer N|| 2≈ε1 with an additional RF field enhancement due to the coupling resonance. The observed spontaneous ETB formation is preceded by an accumulation of high energy ions in the plasma and synchronized with their burst-like outflow to the divertor. On this basis, it is believed that it is fast ion orbit loss that results in formation of a layer with Er shear and E×B velocity shear accordingly at the plasma boundary, this, in turn, resulting in a damping of turbulence and turbulence-induced anomalous transport.